A study on fabrication of nanocomposite polyethylene foam through extrusion foaming procedure. Issue 6 (November 2021) - Rostami, Milad; Azdast, Taher; Hasanzadeh, Rezgar; Moradian, Milad
Foaming a polymer not only turns it into a lightweight material but also gives some special properties to it. However, the most important issue is controlling the foaming process to achieve a desirable structure with high cell density and low relative density. In the present study, the extrusion foaming process of polyethylene was studied through stepwise amendments. An innovative extrusion system was designed and implemented to produce extrusion foams under different material and process conditions using N2 as blowing agent. In the first step, the final cooling condition was investigated. The air-cooling condition led to a higher cell density/lower cell size compared to the water-cooling condition although a higher relative density was obtained. In the second step, the effects of the addition of talc and the synergetic effect of talc/nanoclay at different contents were investigated in detail. The hybrid of talc/nanoclay had a noticeably improving effect on the cellular structure. In the third step, the effects of processing parameters including the die temperature and screw speed were studied on the foam properties. Finally, up to 49.4% decrease in the relative density of samples was observed, also cell densities up to 2.5 × 10 4 cell/cm 3 and cell sizes as small as 280 µm were achieved.